2009
DOI: 10.1093/nar/gkp592
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for high bi-allelic expression of activating Ly49 receptors

Abstract: Stochastic expression is a hallmark of the Ly49 family that encode the main MHC class-I-recognizing receptors of mouse natural killer (NK) cells. This highly polygenic and polymorphic family includes both activating and inhibitory receptor genes and is one of genome's fastest evolving loci. The inhibitory Ly49 genes are expressed in a stochastic mono-allelic manner, possibly under the control of an upstream bi-directional early promoter and show mono-allelic DNA methylation patterns. To date, no studies have d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
5
14
0
Order By: Relevance
“… reported that the co‐expression of Ly49D and Ly49H is non‐stochastic. These two molecules are the only activating Ly49 receptors found in the B6 genome, which is interesting in relation to data suggesting that the non‐stochastic regulation of the activating Ly49 receptors might be due to a distinct mode of transcriptional regulation compared to inhibitory receptors .…”
Section: The Nk Cell Inhibitory Receptor Repertoirementioning
confidence: 59%
“… reported that the co‐expression of Ly49D and Ly49H is non‐stochastic. These two molecules are the only activating Ly49 receptors found in the B6 genome, which is interesting in relation to data suggesting that the non‐stochastic regulation of the activating Ly49 receptors might be due to a distinct mode of transcriptional regulation compared to inhibitory receptors .…”
Section: The Nk Cell Inhibitory Receptor Repertoirementioning
confidence: 59%
“…This reduced expression of Ly49D might be due to interactions with H-2D d in the F1. The percentages of Ly49D ϩ and Ly49H ϩ NK cells in the F1 mice were not exactly half of B6, suggesting that these receptors are expressed in a biallelic manner on at least some NK cells in the F1 mice 25 (Table 1). In addition, in these F1 mice, a higher percentage of Ly49D ϩ NK cells coexpressed more Ly49G2 and lower amounts of Ly49C/I than the Ly49D Ϫ NK-cell subset ( Figure 1B).…”
Section: Nk Cells In Cb6f1 Micementioning
confidence: 99%
“…Based on studies of the expression of Ly49A, C, and G by individual NK cells or clones from F1 mice (36)(37)(38)(39)(40), it is generally believed that the expression of Ly49 receptors is controlled by a probabilistic mechanism in which not only each gene but also each allele of each gene is expressed independently, resulting in a partially monoallelic pattern of expression. However, whether this model applies to all Ly49 receptors is unclear, and evidence has recently been presented that Ly49H is expressed in a normal codominant manner (41). In the case of Ly49E, the limited allelic variation of Ly49E has until now precluded a determination of its pattern of expression.…”
Section: Discussionmentioning
confidence: 99%